Efficacy and safety of ciprofol for long-term sedation in patients receiving mechanical ventilation in ICUs: a prospective, single-center, double-blind, randomized controlled protocol - Sun, Xiaoxiao; Zhang, Meixian; Zhang, Hui; Fei, Xuejie; Bai, Gang; Li, Cheng (Frontiers in Pharmacology, 2023)
Introduction: Critically ill patients who receive mechanical ventilation after endotracheal intubation commonly experience discomfort and pressure. The major sedative drugs that are currently used in clinical practice present with many complications, such as hypotension, bradycardia, and respiratory depression. Ciprofol (HSK3486), which is a newly developed structural analog of propofol, is a short-acting gamma-aminobutyric acid (GABA) receptor agonist, and its mechanism of action is sedation or anesthesia by enhancing GABA-mediated chloride influx. The high efficacy of ciprofol for short-term sedation is comparable to that of propofol, and it has a relatively low incidence of adverse effects and high level of safety, which has been confirmed by multiple clinical studies. However, few studies have examined its safety and efficacy for long-term sedation. The purpose of the study is to evaluate the efficacy and safety of ciprofol for long-term sedation in mechanically ventilated patients.Methods: A prospective, single-center, double-blind, randomized, propofol-controlled, noninferiority trial is proposed. The study will enroll 112 mechanically ventilated patients hospitalized in the intensive care unit (ICU) of the Shanghai Fourth People's Hospital affiliated with Tongji University based on the inclusion and exclusion criteria of the study, and randomly assign them to a group sedated with either ciprofol or propofol. The primary outcome is the percentage of time spent under target sedation, and secondary outcomes include drug dose, number of cases requiring additional dextrometropine, incidence of systolic blood pressure < 80 mmHg or > 180 mmHg, incidence of diastolic blood pressure < 50 mmHg or > 100 mmHg, incidence of heart rate < 50 beats per minute (bpm) or > 120 bpm, inflammatory indicators, blood lipid levels, liver and kidney functions, nutritional indicators, ventilator-free days within the 7-day period after enrollment, 28-day mortality, ICU stay duration, and hospitalization costs.Discussion: We hypothesize that the efficacy and safety of ciprofol for long-term sedation in mechanically ventilated ICU patients will not be inferior to that of propofol.